Effect of Anti-tobacco Health Messages Post-implemetation of COTPA 2003 in India - Laxmi Kumari; Meenakshi Sood; Sandhya Gupta (Indian Journal of Psychiatric Nursing)
Tobacco-related deaths are rising, although it is a preventable man-made epidemic. Globally, tobacco accounts for the death of 6 million people each year. The tobacco industry very intelligently uses the mass media platform for pro-tobacco propaganda messages. India made a significant attempt to fight tobacco by endorsing the WHO Framework Convention on Tobacco Control in February 2004. The WHO has introduced the MPOWER package of six proven policies to reverse the tobacco epidemic and prevent millions of tobacco-related deaths. Surprisingly, with all the awareness about these harms related to tobacco consumption and anti-tobacco campaigns at national and international levels, tobacco users do not feel motivated to quit. Anti-tobacco health messages (ATHMs) are crucial in affecting tobacco-related health behavior. This review summarizes the effect of ATHMs on the Indian population and the influences of different types of ATHMs on motivation to quit tobacco and tobacco cessation as a whole. Depending on the group investigated, ATHM effects on smoking behavior vary. ATHMs can influence people's attitudes and beliefs, improve intentions to stop and quit attempts, and decrease tobacco use dominance. They can also play a crucial role in educating the public about the dangers of tobacco use. The government must concentrate on rational ATHMs with broad appeal, ongoing exposure, and a preference for negative health effects with visual and live testimonial ads.